Big data-driven early alert systems as means of enhancing university student retention and success - Cele, N. (South African Journal of Higher Education, 2021)
This article argues for the establishment of big data early alert systems that inform data-driven student support mechanisms in universities. It proposes a guiding framework for integrated big data to enhance student success premised on a comprehensive understanding of students as people in the world who arrive at universities with various complex life problems that may disrupt their learning opportunities. It argues that various data components should be linked together to foster coherence and seamlessness in understanding student socio-economic and academic needs to develop responsive learning-enhancement intervention programmes. This is based on action research conducted through projects launched at the University of Witwatersrand in 2015 and at the University of Zululand in 2018. The systems were launched, and data was collected using the proposed student performance tracking system. This article explores conceptual and theoretical underpinnings of establishing big data-based student support systems in South African universities. A big student data model is proposed for wider use in South African universities